Development of History Problems Based on Higher Order Thinking Skills (HOTS) Using Anderson Krathwohl Taxonomy - Azis*, Abdul; Nurasiah, Nurasiah (Universitas Syiah Kuala, 2024)
This study aims to 1) analyze the condition of the historical electronic module currently used at SMA Banda Aceh, especially in class XII Indonesian history subjects, 2) describe the development of the historical electronic module that was developed, and 3) describe the feasibility level of the electronic module that has been developed. This research is a type of R D research by adopting the development model of Borg and Gall. To produce this historical electronic module, researchers adopted two stages of development, namely the preliminary research stage and the development research stage. In the preliminary research stage, the researcher conducted a library study and observation. In the development research stage, the researchers carried out module designs, validated with experts and educators, revised, and conducted initial trials on six class XII students at SMA Banda Aceh. The research process was carried out using research instruments in the form of validation sheets and questionnaires. The results showed that 1) the historical electronic module used at SMA Banda Aceh in class XII is a module from the Kemendikbud, 2) the process of developing this module was carried out using Heyzine media in accordance with the advice of experts and educators, the initial trial process was carried out on six students with the final results of PBL-based historical electronic modules for class XII students at SMA Banda Aceh are very suitable for use, with a score of 98% from module experts, 88% from material experts, 86% from educators, and 90% from students.